An investigation of the colorectal cancer experience and receptivity to family-based cancer prevention programs - Breitkopf, Carmen Radecki (Support Care Cancer, 2014)
PURPOSE: Cancer is a shared family experience and may provide a “teachable moment” to motivate at-risk family members to adopt cancer prevention and health promotion behaviors. This study explored how a diagnosis of colorectal cancer (CRC) is experienced by family members and may be used to develop a family-based CRC prevention program. Preferences regarding content, timing, and modes of program delivery were examined. Social cognitive theory provided the conceptual framework for the study. METHODS: This study employed mixed methodology (semi-structured interviews and self-report questionnaires). Participants included 73 adults (21 patients, 52 family members) from 23 families (two patients were deceased prior to being interviewed). Most patients (n=14; 67 %) were interviewed 1–5 years post-diagnosis. Individual interviews were audio-recorded, transcribed, and content analyzed. RESULTS: For many, a CRC diagnosis was described as a shared family experience. Family members supported each other’s efforts to prevent CRC through screening, exercising, and maintaining a healthy diet. Teachable moments for introducing a family-based program included the time of the patient’s initial cancer surgery and post-chemotherapy. Reported willingness to participate in a family-based program was associated with risk perception, self-efficacy, outcome expectancies, and the social/community context in which the program would be embedded. Program preferences included cancer screening, diet/nutrition, weight management, stress reduction, and exercise. Challenges included geographic dispersion, variation in education levels, generational differences, and scheduling. CONCLUSIONS: CRC patients and family members are receptive to family-based programs. Feasibility concerns, which may be mitigated but not eliminated with technological advances, must be addressed for successful family-based programs.